Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
Tìm x
a.( x - 140 ) : 3 = 27
x - 140 = 27 . 3
x - 140 = 81
x = 221
b.14 - 4 ( x + 1 ) = 10
4 ( x + 1 ) = 14 - 10
4 ( x +1) = 4
x + 1 = 1
x = 0
c. 15 ( 7 - x ) = 15
7 - x = 1
x = 6
d.34 ( x - 3 ) = 0
\(\Rightarrow\) 34 = 0 hoặc x - 3 = 0
1. 34 = 0 ( vô lí )
2. x - 3 = 0 \(\Rightarrow\) x = 3
e. 24 + 6 (3 - x ) = 30
6( 3- x ) = 30 - 24
6( 3 - x ) = 6
3 - x = 1
x = 2
f. x3 + 24 = 51
x3 = 51 - 24
x3 = 27
\(\Rightarrow\)x = 3 ; x = -3
g. ( x- 5 )2 - 5 = 44
( x - 5) 2 = 49
\(\Rightarrow\)x - 5 = 7 hoặc x - 5 = -7
1. x - 5 = 7\(\Rightarrow\)x = 12
2. x - 5 = -7 \(\Rightarrow\)x = -2
h. ( x + 1 )3 - 23 = 4
( x + 1 )3 =27
\(\Rightarrow\) x + 1 = 3 hoặc x + 1 = -3
1. x + 1 = 3\(\Rightarrow\)x = 2
2. x + 1 = -3 \(\Rightarrow\)x = -4
![](https://rs.olm.vn/images/avt/0.png?1311)
1
a, 15 - ( 4 - x ) = 6
<=> 4 - x = 6 - 15
<=> 4 - x = -9
<=> x = -9 + 4
<=> x = -5
Mấy câu kia dễ tự làm :>
\(15-\left(4-x\right)=6\)
\(\Rightarrow4-x=9\)
\(\Rightarrow x=-5\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x-14=3x + 18
x - 3x = 18 + 14
-2x = 32
=> x = -16
b) (x+7)(x-9)=0
=> TH1: x+7=0 => x = -7
=> TH2: x-9=0 => x = 9
c) x(x+3) =0
=> TH1: x=0
=> TH2: x+3 =0 => x = -3
d) (x-2)(5-x)=0
=> TH1: x-2=0 => x=2
=> Th2: 5-x=0 => x=5
![](https://rs.olm.vn/images/avt/0.png?1311)
a; \(\dfrac{93}{17}\): \(x\) + (- \(\dfrac{21}{17}\)) : \(x\) + \(\dfrac{22}{7}\): \(\dfrac{22}{3}\) = \(\dfrac{5}{14}\)
\(\dfrac{94}{17}\) \(\times\) \(\dfrac{1}{x}\) - \(\dfrac{21}{17}\) \(\times\) \(\dfrac{1}{x}\) + \(\dfrac{3}{7}\) = \(\dfrac{5}{14}\)
\(\dfrac{72}{17}\) \(\times\) \(\dfrac{1}{x}\) + \(\dfrac{3}{7}\) = \(\dfrac{5}{14}\)
\(\dfrac{72}{17x}\) = \(\dfrac{5}{14}\) - \(\dfrac{3}{7}\)
\(\dfrac{72}{17x}\) = - \(\dfrac{1}{14}\)
17\(x\) = 72.(-14)
17\(x\) = - 1008
\(x\) = - 1008 : 17
\(x\) = - \(\dfrac{1008}{17}\)
Vậy \(x\) \(=-\dfrac{1008}{17}\)
b; - \(\dfrac{32}{27}\) - (3\(x\) - \(\dfrac{7}{9}\))3 = - \(\dfrac{24}{27}\)
- \(\dfrac{32}{27}\) + \(\dfrac{24}{27}\) = (3\(x\) - \(\dfrac{7}{9}\))3
(3\(x-\dfrac{7}{9}\))3 = - \(\dfrac{8}{27}\)
(3\(x-\dfrac{7}{9}\))3 = (- \(\dfrac{2}{3}\))3
3\(x-\dfrac{7}{9}\) = - \(\dfrac{2}{3}\)
3\(x\) = - \(\dfrac{2}{3}\) + \(\dfrac{7}{9}\)
3\(x\) = \(\dfrac{1}{9}\)
\(x\) = \(\dfrac{1}{9}\) : 3
\(x\) = \(\dfrac{1}{27}\)
Vậy \(x=\dfrac{1}{27}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
d) |2x – 5| –7 = 22
| 2x -5 | = 22+7
| 2x -5 | = 29
TH1: 2x-5 = -29
2x = -29+5
2x= -24
x= -24:2
x= -12
TH2: 2x -5 =29
2x = 29+5
2x= 34
x= 34:2
x= 17
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a) 02002 < 02023
b) 20220 = 20230
c) 549 < 5510
d) ( 4 + 5 )3 > 42 + 52
đ) 92 - 32 > ( 9 - 3 )2
Bài 2:
a) 32 x 43 - 32 + 333
= 9 x 64 - 9 + 333
= 576 - 9 + 333
= 567 + 333
= 900
b) 5 x 43 + 24 x 5 + 410
= 5 x 64 + 24 x 5 + 1
= 5 x ( 64 + 24 ) + 1
= 5 x 88 + 1
= 440 + 1
= 441
c) 23 x 42 + 32 x 5 - 40 x 12023
= 8 x 16 + 9 x 5 - 40 x 1
= 128 + 45 - 40
= 133
Bài 1 :
a) \(0^{2002}=0;0^{2023}=0\Rightarrow0^{2002}=0^{2023}\)
b) \(2022^0=1;2023^0=1\Rightarrow2022^0=2023^0\)
c) \(54^9< 55^9;55^9< 55^{10}\Rightarrow54^9< 55^{10}\)
d) \(\left(4+5\right)^3>\left(4+5\right)^2;\left(4+5\right)^2>4^2+5^2\Rightarrow\left(4+5\right)^3>4^2+5^2\)
đ) \(9^2-3^2=81-9=82;\left(9-3\right)^2=6^2=36\Rightarrow9^2-3^2>\left(9-3\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) \(x\left(5-x\right)=0\Leftrightarrow\left[{}\begin{matrix}x=0\\x=5\end{matrix}\right..\)
Vậy .....
b ) \(\left(3-x\right)\left(x^2+1\right)=0\Leftrightarrow\left[{}\begin{matrix}3-x=0\\x^2+1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=3\\x^2=-1\left(loại\right)\end{matrix}\right.\)
Vậy ........
c ) giống câu b
d ) \(\left(2x-1\right)^3=8\Leftrightarrow2x-1=2\Leftrightarrow\Leftrightarrow x=\dfrac{3}{2}\)
e ) \(\left(x+3\right)^2=16\Leftrightarrow\left[{}\begin{matrix}x+3=4\\x+3=-4\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=1\\x=-7\end{matrix}\right.\)
Vậy.
a. 2 x 3^2 - 24 : ( 3^100 : 3^99 )
= 2 x 9 - 24 : ( 3 1 00 - 99 )
= 2 x 9 - 24 : 3
= 18 - 8
= 10
b. 9 x 2^2 : ( 14^0 + 1^2022 )
= 9 x 4 : ( 1 + 1)
= 36 : 2
= 18
c. 3 x { 9 + 3 x [ 30 - ( 5^2 - 22 )]}
= 3 x { 12 x [ 30 - ( 25 - 22) ] }
= 3 x { 12 x ( 30 - 3 ) }
= 3 x ( 12 x 27)
= 3 x 324
= 972
a.\(2.3^2-\left(3^{100}:3^{99}\right)\)
\(=2.9-\left(3^1\right)\)
\(=18-3\)
\(=15\)
b. \(9.2^2:\left(14^0+1^{2022}\right)\)
\(=9.4:\left(1+1\right)\)
\(=36:2\)
\(=18\)
c.\(3.\left\{9+3.\left[30-\left(5^2-22\right)\right]\right\}\)
\(=3.\left\{9+3.\left[30-\left(25-22\right)\right]\right\}\)
\(=3.\left\{9+3.\left[30-3\right]\right\}\)
\(=3.\left\{9+3.27\right\}\)
\(=3.\left\{9+81\right\}\)
\(=3.90\)
\(=180\)